CSIG-10. ROLE OF c-Met/β1 INTEGRIN COMPLEX IN THE ESTABLISHMENT OF BRAIN METASTASES. (11th November 2019) - Wadhwa, Harsh; Lau, Darryl; Chandra, Ankush; Nguyen, Alan; Shah, Sumedh; Spatz, Jordan; Safaee, Michael; Sudhir, Sweta; Patel, Akshar; Cheng, Justin; Aghi, Manish
Abstract: INTRODUCTION: Metastases cause 90% of human cancer deaths. The metastatic cascade involves five steps: invasion, intravasation, extravasation, colonization, and proliferation. While individual mediators of these processes have been investigated, their interactions remain undefined. We previously demonstrated increased formation of a structural complex between receptor tyrosine kinase c-Met and β1 integrin in metastases compared to primary tumors. We used novel cell culture models and in vivo assays to define the role of this complex in individual steps of the metastatic cascade. METHODS: The iDimerize heterodimer system was inserted into MDA-MB-231 breast adenocarcinoma cells, allowing c-Met/β1 heterodimerization induction via A/C heterodimerizer treatment. Scratch assays and novel transwell assay modifications were used to measure migration, invasion, intravasation, and extravasation. Proximity ligation assay was performed to measure c-Met/β1 complex. Nanostring panel was used to transcriptionally profile cells. RESULTS: c-Met/β1 complex induction promotes breast cancer invasion (p< 0.001), migration (p< 0.05), intravasation (p< 0.01), and adhesion to the vessel wall (p< 0.01). However, it does not increase extravasation in culture or in vivo. These effects may be driven by the ability of c-Met/β1 to increase mesenchymal character (p< 0.05) and stem cell population (p< 0.001). Nanostring analysis revealed upregulated Wnt and hedgehog pathways after c-Met/β1 complex induction, particularly WNT7B (p< 0.05). OS2966, an antibody preventing c-Met/β1 binding, decreased invasion (p< 0.05), intravasation (p< 0.05), and mesenchymal morphology (p< 0.001) and gene expression (p< 0.001). Brain- and bone-seeking breast cancer cells have higher c-Met/β1 complex than controls (p< 0.05) and preferentially adhere to tissue-specific matrix (p< 0.01). CONCLUSIONS: The c-Met/β1 complex drives breast cancer cell intravasation. While extravasation is not affected by the complex, preferential affinity for tissue-specific matrix enables the c-Met/β1 complex to drive breast cancer metastases to brain and bone. Pharmacological targeting of the complex may prevent metastases, particularly to the brain and bone.